Multiband reconfigurable antenna using EBG unit cells - Dewan, R. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper presents the design of multiband reconfigurable antenna using metamaterial Electromagnetic Band Gap (EBG) unit cells. The two EBG unit cells were position underneath the feeding of the antenna. By implementing the band gap characteristics of the EBG, the antenna can be reconfigured at various multiband frequencies simultaneously. The EBG band gap characteristics of the EBG unit cells were manipulated by varying the EBG configurations, namely 0000, 0101, 1010, and 1111. The band gaps are at 2.45 GHz, 3.6 GHz, 1.8 GHz, 2.8 GHz and 5.5 GHz. The multiband reconfigurable frequencies are (but not limited to) 2.67, 3.21, 3.78 and 5.15 1.80 GHz, 3.83 GHz and 5.25 2.32, 2.70, 3.23, 3.76 and 5.30 2.57, 3.83 and 4.67 GHz. The proposed antenna has the potential to be use for various wireless communications services.